Minimally Invasive Coronary Artery Bypass Grafting in a Patient With Chronic Tracheostoma: Alternative to Reduce Sternal Wound Complication Risk. Issue 6 (November 2022) - Nantsios, Alex; Elmistekawy, Elsayed; Ponnambalam, Menaka; Lambert, A. Stephane; Ruel, Marc
Patients with chronic tracheostoma present a challenge when they require coronary bypass surgery due to an elevated risk of sternal wound infections (SWI). Minimally invasive coronary artery bypass grafting (MICS CABG) is a robust technique that allows complete surgical revascularization while mitigating the risks of sternal complications and functional decline associated with sternotomy. In such patients at elevated risk for SWI, MICS CABG may represent a viable revascularization strategy to avoid sternotomy. Here, we present a case of a frail, comorbid patient with a chronic tracheostomy and symptomatic multivessel coronary artery disease not amenable to percutaneous therapy referred for MICS CABG.